Integrated Plasma Metabolomics and Gut Microbiota Analysis: The Intervention Effect of Jiawei Xiaoyao San on Liver Depression and Spleen Deficiency Liver Cancer Rats - Li, Zhuoxian; Zhao, Youxing; Cheng, Jinlai; Xu, Lijing; Wen, Xiaoyu; Sun, Yuhao; Xia, Meng; He, Yining (Frontiers in Pharmacology, 2022)
GRAPHICAL ABSTRACT